Contemporary Developments in Emergent Literatures and the New Europe - Domínguez, César; O'Dwyer, Manus (ES Servizo de Publicacións e Intercambio Científico da USC, 2014)
Contemporary Developments in Emergent Literatures and the New Europe seeks to explore changing conceptions of European identity, and the possible ways in which we can speak of a "N/new Europe", in the context of a discussion of the concept of literary emergence. It gathers a group of both established and early career researchers, from diverse parts of Europe, US and South Africa, whose readings of literary texts describe a range of deterritorialized, hybrid, and heterogeneous identities. Tracing paths from the West of Ireland to Albania, from London to Mecca and Argentina, the essays collected here reveal a Europe that is porous and multiethnic, a Europe of the mind whose spatial co-ordinates exceed national boundaries and divisions. This volume provokes us to reassess our conceptions of the "Old" Europe, to draw from the new voices we hear in its pages a new landscape, or a palimpsestic overlaying of distinct maps.
Keywords: Libros electrónicos